Consumer Purchasing Decisions: The Influence of Green Product, E-Branding, and Consumer Knowledge - Muhammad Deny; Agus Rahayu; Henny Hendrayati (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study analyzes the influence of green products and consumer knowledge, mediated through e-branding, on purchasing decisions of Pertamax series consumers amid environmental concerns like global warming and vehicle emissions. Research Methodology: A purposive probability sampling approach collected data from 200 Pertamax consumers. Path analysis using IBM SPSS Statistics 26 was employed to examine the relationships. Results: The analysis revealed three key findings: First, green products and consumer knowledge positively impact e-branding and purchasing decisions. Second, green products, consumer knowledge, and e-branding collectively influence purchasing decisions positively. Third, E-Branding does not mediate the relationship between green products and consumer knowledge in influencing purchasing decisions. Conclusions: Green products and consumer knowledge significantly drive purchasing behavior, both directly and in conjunction with e-branding. However, E-Branding does not serve as a mediating mechanism between these factors and purchase decisions. Therefore, marketing strategies should prioritize enhancing the perceived value of green products and improving consumer environmental literacy directly Limitations: The study is limited to 200 respondents from a specific consumer segment (Pertamax users), which may restrict the generalizability of the findings to broader populations or other green product categories. Contributions: This research contributes to the fields of sustainable marketing and consumer behavior by clarifying the roles of green product attributes and consumer knowledge in shaping eco-conscious purchasing decisions in the digital age. The findings offer practical insights for energy companies, marketers, and policymakers aiming to promote environmentally friendly fuel alternatives through effective digital branding and consumer education strategies.